Correlation Of Serum Calcium Level with Gold Criteria in Chronic Obstructive Pulmonary Disease Patients in A Tertiary Care Centre Tamaka Kolar - reddy sangam, Prem chandar; Raveesha A, Raveesha A; CR, Vidyasagar; Gowda B G, Manohar (Journal of Neonatal Surgery, 2025)
Introduction Patients with acute exacerbation of chronic obstructive pulmonary disease (COPD) are at increased risk for morbidity and mortality compare to non-exacerbators. Electrolyte imbalances with calcium is most often reported in these patients. Correlation between serum calcium levels and GOLD (Global Initiative for Chronic Obstructive Lung Disease) criteria remains unclear. Aims and objectives This study aims to correlate serum calcium levels in acute exacerbation of COPD patients with GOLD criteria. Materials and Methods Forty-eight (48) patients with acute exacerbation of COPD were included in the study. Serum calcium levels were defined as per recent guidelines.Statistical analysis was performed using SPSS version 22. Results A total of 48 patients were included in which majority of people were between the ages 61and 70. The mean serum calcium levels were lower in patients with acute exacerbation of chronic obstructive pulmonary disease in which very low serum calcium level correlated with severe grade of GOLD criteria(viceversa) with significant p value of <0.05. Conclusion Our study indicated that hypocalcemia was associated with an elevated risk of COPD exacerbation.Hypocalcemia was correlated with GOLD criteria, the low the serum calcium level the severe the GOLD criteria.